A Second Amorphous Layer Underneath Surface Oxide. (23rd February 2017) - Zhang, Bin; Peng, Kunlin; Sha, Xuechao; Li, Ang; Zhou, Xiaoyuan; Chen, Yanhui; Deng, QingSong; Yang, Dingfeng; Ma, Evan; Han, Xiaodong
Abstract: Formation of a nanometer-scale oxide surface layer is common when a material is exposed to oxygen-containing environment. Employing aberration-corrected analytical transmission electron microscopy and using single crystal SnSe as an example, we show that for an alloy, a second thin amorphous layer can appear underneath the outmost oxide layer. This inner amorphous layer is not oxide based, but instead originates from solid-state amorphization of the base alloy when its free energy rises to above that of the metastable amorphous state; which is a result of the composition shift due to the preferential depletion of the oxidizing species, in our case, the outgoing Sn reacting with the oxygen atmosphere.